PENERAPAN METODE COOPERATIVE LEARNING DALAM PEMBELAJARAN MENULIS TEKS IKLAN, SLOGAN, DAN POSTER UNTUK PENINGKATAN AKTIVITAS DAN KREATIVITAS SISWA KELAS VIII SMP PASUNDAN 2 BANDUNG - Nurhayatin, Titin; Rustandi, Adi; Nugraha, Eggie; Kusmini, Anne (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
This research is motivated by learning conditions that are still not optimal, both process and learning outcomes. Therefore, we conducted a research to apply lesson study by using the Cooperative Learning method in Indonesian Language, in writing advertisement, slogans, and posters texts in class VIII of Pasundan 2 Junior High School Bandung. This research is expected to improve learning outcomes, activities and creativities. The research method used is an experimental method. The research subjects were students of Pasundan 2 Bandung Junior High School Class VIII C. This research was an implementation of plan, do and see. The validity of the data is done through triangulation techniques. Based on the results of the study it can be concluded that the application of lesson study using the Cooperative Learning method is carried out in accordance with the stages in the lesson study, namely plan, do and see. Lesson study makes the learning planning process more mature so that in the implementation of learning the model lecturer feels more prepared. Lesson Study can effectively improve the quality of learning, both processes and results. This can be seen from the test results which are tested on the average significant improvement. Likewise in the process, based on the observations made, the activity and creativity of students of Pasundan 2 Junior High School Bandung increased. Thus, it can be concluded that the implementation of lesson study with cooperative learning effectively increases the activity, creativity, and learning outcomes of students in Pasundan 2 Junior High School Bandung significantly.